Auditor tenure, managerial fraud and report qualification: a behavioural game-theoretic approach. (3rd November 2008) - Fairchild, Richard
We consider the effect of auditor tenure on the level of managerial fraud and the extent of auditor qualification of reports. We consider two conflicting effects. As auditor tenure increases, the auditor's ability to detect fraud increases (the 'learning curve' effect), which reduces the manager's fraud-incentives. On the other hand, the auditor may become more sympathetic towards management (the 'loss of independence' effect), which may increase fraud incentives. In order to analyse these issues, we develop an auditing game in which the manager makes an unobservable decision whether or not to commit fraud. The auditor then decides whether to perform a basic or an extended audit. The level of audit affects the probability of fraud-detection. Following the outcome of the audit, the auditor then decides whether to issue a qualified or unqualified report. In equilibrium, the effect of auditor tenure on fraud and report qualification depends on whether the auditor's ability or the auditor's loss of independence dominates. We consider the ethical dimensions of our model, and we provide policy implications in relation to the ongoing debate regarding mandatory turnover of auditors.